Antioxidant and redox regulation of genes - Sen, Chandan K.; Sies, H.; Baeuerle, P. A. (Academic Press, 2000)
Signaling by singlet oxygen in biological systems / Lars-Oliver Klotz, Karlis Briviba, and Helmut Sies -- Redox regulation of gene expression / Dana R. Crawford, Toshihide Suzuki, and Kelvin J.A. Davies -- Rac, superoxide, and signal transduction / Hamdy H. Hassanain and Pascal J. Goldschmidt-Clermont -- Redox regulation of ion channels / Suneil K. Koliwad, Anna K. Brzezinska, and Stephen J. Elliot -- Cell Ca 2 in signal transduction : modulation in oxidative stress / Julio Girón-Calle and Henry Jay Forman -- Induction of protein tyrosine phosphorylation by oxidative stress and its implications / Gary L. Schieven -- Regulation of signal transduction and gene expression by reactive nitrogen species / Ami A. Deora and Harry M. Lander -- Reactive oxygen species as costimulatory signals of cytokine-induced NF-[kappa]B activation pathways / Patrick A. Baeuerle -- Redox regulation of NF-[kappa]B / Takashi Okamoto ... [et al.] -- Oxidants and antioxidants in apoptosis : role of Bcl-2 / Chandan K. Sen -- Role of reactive oxygen species in tumor necrosis factor toxicity / Vera Goossens ... [et al.] -- Redox regulation of cell adhesion processes / Sashwati Roy ... [et al.] -- Role of thioredoxin and redox regulation in oxidative stress response and signaling / Hiroshi Masutani ... [et al.] -- Redox regulation of p21, role of reactive oxygen and nitrogen species in cell cycle progression / Axel H. Schönthal, Sebastian Mueller, and Enrique Cadenas -- Effects of lipoxygenases on gene expression in mammalian cells / Helena Vitta and Seppo Ylä-Herttuala -- [alpha]-tocopherol in the pathogenesis of atherosclerosis : one molecule, several functions / Angelo Azzi -- Peroxiredoxins in cell signaling and HIV infection / Dong-Yan Jin and Kaun-The Jeang -- Enhanced activity of an oxidation product of lycopene found in tomato products and human serum relevant to cancer prevention / John S. Bertram ... [et al.] Antioxidant genes and reactive oxygen species in Down's syndrome / Cécile Bladier, Judy B. de Haan, and Ismail Kola -- Oxidant-mediated repression of mitochondrial DNA transcription / Bruce S. Kristal and Byung P. Yu -- Suppression of insulin gene promoter activity by oxidative stress / Yoshitaka Kajimoto ... [et al.] -- Redox regulation of ischemic adaptation / Nilanjana Maulik and Dipak K. Das -- Oxidative stress as a governing factor in physiological aging / William C. Orr and Rajindar S. Sohal -- Antioxidants in senescence and wasting / Wulf Dröge ... [et al.]